O budismo da “Verdadeira Escola da Terra Pura”: uma análise do amidismo japonês entre a mística e a filosofia da religião - Souza, Fernando Rodrigues de (2024)
This dissertation analyzes the True Pure Land Buddhism, also called Amidism, a religious tradition in Japan, which has its foundation attributed to the monk Shinran Shonin (1173-1263), exploring its main religious, philosophical and mystical aspects. The methodologies used are bibliographical review and textual hermeneutics, carried out through the examination of the sutras and the critical review of the literature produced by commentators, aiming at discussing the foundations of the doctrine of the Pure Land, providing subsidies that overcome the difficulties existing in the different perspectives on the topic. The research highlights how amidism transcends mere ritualistic devotion, involving a deep philosophical reflection on the nature of salvation and the relationship between faith and spiritual practice. Furthermore, the elements that distinguish this school within Japanese Buddhism are examined, placing it within the panorama of Mahayana Buddhist traditions. The study also aims to contribute to a broader understanding of the religious and spiritual dynamics of Japanese Amidism, investigating how it integrates mystical and philosophical aspects to offer a comprehensive approach to spiritual quest within the Buddhist context, providing a well-founded view and deepening the understanding of the doctrine taught by Shinran Shonin. Furthermore, it is intended to inspire future research capable of further enriching knowledge about how mysticism and philosophy are intertwined in religious traditions.